2021
DOI: 10.3390/agronomy11050869
|View full text |Cite
|
Sign up to set email alerts
|

Organo-Mineral Interactions Involved in Herbicide Sorption on Soil Amended with Peats of Different Maturity Degree

Abstract: The sorption of three herbicides (alachlor, atrazine and linuron) on samples from six peats of progressive degree of maturity (fibric, hemic or sapric types) and soil samples (dryland agricultural Calcic Luvisol amended with the peats) was determined. The extent of the sorption was examined in terms of peat maturity (up to 220 analytical descriptors of the peat material). In most cases, a sorption enhancement effect was observed in the peat–soil system compared with the sum of the sorption in peat and soil alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 46 publications
(46 reference statements)
0
3
0
3
Order By: Relevance
“…However, insecticide uptake on the loam soil material was attributed solely to montmorillonite, presumably due to the enhanced physical diffusion of the pesticide into Mt interlayers, governed by van der Waals forces [ 71 ]. It is commonly observed that the particulate organic (or organo-mineral) soil fractions form stable microaggregates where the retention of pesticides could depend more on steric factors and diffusion mechanisms than on the type and amounts of oxygen-containing functional groups [ 72 ]. Therefore, both organic (mainly CR) and inorganic (Mt) soil colloids contribute to carbofuran retention in the studied soils via hydrophobic bonding and van der Waals forces.…”
Section: Resultsmentioning
confidence: 99%
“…However, insecticide uptake on the loam soil material was attributed solely to montmorillonite, presumably due to the enhanced physical diffusion of the pesticide into Mt interlayers, governed by van der Waals forces [ 71 ]. It is commonly observed that the particulate organic (or organo-mineral) soil fractions form stable microaggregates where the retention of pesticides could depend more on steric factors and diffusion mechanisms than on the type and amounts of oxygen-containing functional groups [ 72 ]. Therefore, both organic (mainly CR) and inorganic (Mt) soil colloids contribute to carbofuran retention in the studied soils via hydrophobic bonding and van der Waals forces.…”
Section: Resultsmentioning
confidence: 99%
“…The type of soil clay mineral becomes especially important when the soil organic carbon contents are low [13]. The extent to which clay minerals contribute to sorption depends on the nature of the pesticide, as well as the ratio of clay mineral to organic carbon fractions of the soil [14,15]. The latter is particularly important in soils abundant in organic matter, as both-mineral and organic types of colloids-might interfere with each other, modulating the number of potential sorption sites for xenobiotics.…”
Section: Introductionmentioning
confidence: 99%
“…Por outro lado, a redução na disponibilidade destes compostos, em sistemas de cultivo contendo palhada, principalmente de aveia preta, podem contribuir com a redução dos riscos e dissipação ambiental de herbicidas. Nesse sentido, é possível pontuar os fatores que afetam a retenção de herbicidas em materiais orgânicos (por exemplo, na palhada) são (I) quantidade e tipo de palhada, (II) composição dessa palhada, (III) grau de decomposição, (IV) caráter hidrofílico e hidrofóbico dos constituintes do material, (V) o processo de decomposição e as (VI) interações das características físico-químicas do produto com o material Li et al, 2017;Dorado;Almendros, 2021).…”
Section: Lixiviação De Diclosulam E Diuron Em Diferentes Palhadasunclassified
“…A sorção-dessorção e a lixiviação são processos que regulam a concentração do herbicida no solo. Esses processos são influenciados por fatores físicos e químicos envolvidos na interação pesticida e material orgânico (Jensen et al, 2018;Dorado et al, 2021). Por exemplo, após a aplicação do herbicida a palhada atua como uma barreira física, sendo necessária a água da chuva ou da irrigação para carrear o herbicida para o solo (Tofoli et al, 2009).…”
Section: Introductionunclassified
See 1 more Smart Citation